The economics of MotoGP : costs, financing and the competitive balance of a raising motorsport - Mourão, Paulo Reis, 1978-; Macedo, Anthony; Sánchez Carreira, María del Carmen (Palgrave Macmillan, 2025)
This book provides insight into the economics of MotoGP and critically analyses the huge amounts of money, employees, racers, directors, and investors involved in the sport. It outlines the costs of MotoGP and the financing of both the teams and the competition itself, highlighting the importance of advertising and broadcasting within the sport's economic model. Through applying ideas of supply and demand and equilibrium value to MotoGP, an understanding of how certain teams and racers perform better than others is outlined, alongside a look at the competitive nature of the sport and what is needed to survive within it. Broader issues, including the political economy of MotoGP, technological innovation, and the ecological footprint of motorsport, are also discussed. This book offers a unique perspective on the operations of MotoGP and how the sport has grown over recent years to have an audience of dozens of millions of viewers per race. It will be relevant to students and researchers interested in sports economics and general readers interested in MotoGP. Paulo Reis Mourão is Associate Professor of Economics at the University of Minho and a Full Member of NIPE (Centre for Research in Economics and Management). Anthony Macedo is an Assistant Professor at the Universidade Lusófona and an Invited Professor at the University of Minho. María del Carmen Sánchez-Carreira is Associate Professor at the Department of Applied Economics of the Faculty of Economics, ICEDE Research Group, and CRETUS at the University of Santiago de Compostela.